FORMULATION AND EVALUATION OF POLYHERBAL CREAM - CHAVAN, PRASHANT; KALSHETTI, MALLINATH; NAVINDGIKAR, NIKHIL (International Journal of Current Pharmaceutical Research, 2020)
Objective: Eugenia caryophyllus, Zingiber officinale and Nyctanthes arbor-tristis are medicinal plants; these plants are used traditionally from ancient year in the various herbal medicinal system such as Ayurvedic, Homeopathic and Siddha. The clove buds of Eugenia caryophyllus, rhizomes of Zingiber officinale and dried leaves of Nyctanthes arbor-tristis have anti-inflammatory analgesic activity. The present research was focus on the formulation of polyherbal cream and their evaluation by using various evaluation parameters of the present research are to formulate polyherbal cream and to evaluate the polyherbal cream. Methods: the slab method was used for the preparation of cream. Results: The evaluation parameters are coming under this heading physical parameter like color was slightly white green, the odor was characteristics, consistency was smooth and the state was semisolid. PH of the cream was 6.5; Spreadability was 7.4g. cm/sec time required for this test was 15 sec, Washability was easily washable, the cream was nonirritant, viscosity of the formulated cream was 39010 cps and no phase separation was observed during storage of polyherbal cream. Conclusion: This cream formulation was used in rheumatoid arthritis to reduce joint pains. This cream formulation was o/w type of emulsion; hence this formulation was easily washed with plane water after application.